2018
DOI: 10.3144/expresspolymlett.2018.56
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porous zeolite on temperature-dependent physical properties of polypropylene/octadecane (PP/OD) composite films

Abstract: Abstract. Polymeric materials with temperature-dependent gas permeabilities using a phase change material are designed and their applicability as a packaging system investigated. Polypropylene/octadecane/zeolite (PP/OD/ZL) composite films were prepared via extrusion process. ZL was used as a filler to enhance the dispersion and interfacial interaction between the OD and the PP originating from different flowabilities during the extrusion process. (FTIR) and (WAXD) analyses showed that the incorporation of ZL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…As a result, the internal structure was more organized than LDPE, contributing to better barrier properties (4) . Kim et al (2018) touched upon the physical properties (DSC) of composite mixed with zeolite agent related to OTR and WVTR of the composite (28) , which was consistent with DSC in this research, as shown in [Figure 2 (a), (b)]. Thus, it is possible that this might not also affect the OTR and WVTR rates of plastic films.…”
Section: Barrier Propertiessupporting
confidence: 86%
“…As a result, the internal structure was more organized than LDPE, contributing to better barrier properties (4) . Kim et al (2018) touched upon the physical properties (DSC) of composite mixed with zeolite agent related to OTR and WVTR of the composite (28) , which was consistent with DSC in this research, as shown in [Figure 2 (a), (b)]. Thus, it is possible that this might not also affect the OTR and WVTR rates of plastic films.…”
Section: Barrier Propertiessupporting
confidence: 86%